Sovereignty in Ruins : A Politics of Crisis (Book collections on Project MUSE., 2017)
Featuring essays by some of the most prominent names in contemporary political and cultural theory, Sovereignty in Ruins presents a form of critique grounded in the conviction that political thought is itself an agent of crisis. Aiming to develop a political vocabulary capable of critiquing and transforming contemporary political frameworks, the contributors advance a politics of crisis that collapses the false dichotomies between sovereignty and governmentality and between critique and crisis. Their essays address a wide range of topics, such as the role history plays in the development of a politics of crisis; Arendt's controversial judgment of Adolf Eichmann; Strauss's and Badiou's readings of Plato's Laws; the acceptance of the unacceptable; the human and nonhuman; and flesh as a biopolitical category representative of the ongoing crisis of modernity.